The Effect Of Tax Rates And Dividend Policy On Share Price In The Banking Sector Listed On The Indonesia Stock Exchange For The 2017-2019 Period - Lestari, Indah; Abubakar, Ibrahim (Sinergi International Journal of Economics, 2023)
One of the main types of investment that promises substantial returns for investors is investing in stocks. However, investing in stocks also carries risks. This dividend policy is a decision in determining the largest profit contribution with the lowest investment risk. The amount of tax rate that will be borne will affect the rise and fall of share prices in each company. Based on the results of the simultaneous regression test involving the independent variables Tax Rate and Dividend Policy on the dependent variable Stock Price, it was found that the f-count value is greater than the f-table with a significance level of F less than 0.05. This shows that the Tax Rate and Dividend Policy variables together have a significant effect on the Share Price variable.